Geografi Terapan: Pengenalan Alat Survei dan Sistem Informasi Geografis bagi Siswa Sekolah Menengah Atas: Applied Geography: Introduction to Survey Instruments and Geographic Information Systems for High School Students - Armin Subhani; Baiq Ahda Razula Apriyeni; Susmala Dewi; Suroso Suroso; Hasrul Hadi; Nurlaila Mubarokah (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
One effort to improve the quality of education is to enhance the quality of learning and provide professional educators. Teachers play a crucial role in the learning process, including the use of appropriate strategies and media. Engaging instructional media is essential for effective communication and interaction in the classroom. Media can include people, materials, or events that help students acquire knowledge and skills. Survey instruments and Geographic Information Systems (GIS) applications are effective instructional media but have not been fully utilized by teachers. This community service activity aimed to introduce survey instruments and GIS applications to students at three schools: SMAN 1 Suela, SMAS NW Tebaban, and MAS NW Tembeng Putik. The activities were conducted in three sessions: March 10, 2023, September 15, 2023, and November 24, 2023. The methods used included lectures, Q&A sessions, demonstrations, hands-on practice, and field observations. The results showed an increase in students' understanding and skills in using survey instruments and GIS applications. At SMAN 1 Suela, 80% of students understood the use of survey instruments such as GPS and geological compasses, and 75% could perform measurements and data collection. At SMAS NW Tebaban and MAS NW Tembeng Putik, 90% of students were able to create maps using the Quantum GIS application. This activity also increased students' interest in studying geography and related sciences. In conclusion, the introduction and guidance on survey instruments and GIS applications are crucial for enhancing students' understanding and skills in geography, making learning more applicable and beneficial